2004
DOI: 10.1063/1.1812823
|View full text |Cite
|
Sign up to set email alerts
|

Prism coupling technique investigation of elasto-optical properties of thin polymer films

Abstract: The use of thin polymer films in optical planar integrated optical circuits is rapidly increasing. Much interest, therefore, has been devoted to characterizing the optical and mechanical properties of thin polymer films. This study focuses on measuring the elasto-optical properties of three different polymers; polystyrene, polymethyl-methacrylate, and benzocyclobutane. The out-of-plane elastic modulus, refractive index, film thickness, and birefringence of thin polymer films were determined by means of the pri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
1

Year Published

2005
2005
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 55 publications
(24 citation statements)
references
References 32 publications
1
20
1
Order By: Relevance
“…Birefringence measurements of spun coat and annealed PS films (150 kg=mol, 2:3 m) have established out-ofplane alignment on oxide coated wafers [16]. Additional studies have shown that the thermal conductivity of polymer microscale films can increase by a factor 4-8 in the direction of alignment [14].…”
Section: Prl 106 175501 (2011) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…Birefringence measurements of spun coat and annealed PS films (150 kg=mol, 2:3 m) have established out-ofplane alignment on oxide coated wafers [16]. Additional studies have shown that the thermal conductivity of polymer microscale films can increase by a factor 4-8 in the direction of alignment [14].…”
Section: Prl 106 175501 (2011) P H Y S I C a L R E V I E W L E T T Ementioning
confidence: 99%
“…24 The deviation is of the order of 10 −4 and depends on the viscoelastic properties of the polymer. 25 Shorter wavelengths can support higher numbers of modes than the longer ones.…”
Section: Resultsmentioning
confidence: 99%
“…This eliminates the possibility of stress induced artefacts in the measurement of refractive indices. This is especially important in the refractive index measurements of soft materials such as some polymers [2]. We applied this technique to measure the refractive index of SiON slab waveguides with a precision of the order of 10 −4 .…”
Section: Discussionmentioning
confidence: 99%
“…In the prism coupling approach, adjustment of the gap between the prism and the waveguide is critical and requires significant pressure, with the associated possibility of damage to the waveguide or the prism [1,2]. Also, the bulky nature of the prism makes it unsuitable for applications in integrated devices.…”
Section: Introductionmentioning
confidence: 99%